FRAUD PENTAGON THEORY FOR DETECTING FINANCIAL STATEMENT FRAUD IN BANKING INDUSTRY - Aileen, Aileen; Salim, Susanto (International Journal of Application on Economics and Business, 2025)
Financial statement fraud is an intentional misstatements, omissions or disclosure in financial statement done by an individual or a party to mislead financial statement users when making decisions. Financial statement fraud committed by irresponsible parties for their own advantage can lead to long-term losses. The purpose of this study is to examine the effects of fraud pentagon theory for detecting financial statement fraud in banking companies listed in the Indonesia Stock Exchange for 2020-2022 period. This study was analysed using multiple regression research method which processed using SPSS 25. The data used in this study was secondary data from financial statement and annual reports. This study used purposive-sampling technique with sample of 90 data observations. The results of this study shows that financial stability and changes in auditor have a significant and negative effect on financial statement fraud. Meanwhile external pressure, monitoring effectiveness, changes in director, and frequent number of CEO’s picture in annual report have no significant effects on financial statement fraud.